Writing Anxiety and Its Impact on EFL Students’ Academic Performance: A Qualitative Study in an English Education Program - Dita Adawiyah; M Daffa Ghazan; Weam Kisa Ulandari (Indonesian Language Education and Applied Linguistics Reviews, 2025)
Academic writing is an important skill for EFL (English as a Foreign Language) students, but many still face writing anxiety. This anxiety makes students feel nervous, afraid of making mistakes, and often leads to procrastination or low confidence. The aim of this study was to explore the forms of writing anxiety and to see how a writing program could help reduce it. This research used a qualitative descriptive design with six undergraduate students from the English Education Study Program at a private university in Palembang, Indonesia. Data were collected through open-ended questionnaires, classroom observations, reflection notes, and students’ essays. The results showed four main forms of writing anxiety: fear of negative evaluation, difficulty starting, lack of confidence in grammar and vocabulary, and avoidance behavior. After joining process writing workshops, peer feedback sessions, and reflective discussions, students became more confident, less anxious, and their essays improved in organization and coherence. The program also encouraged them to collaborate and communicate better with peers. These findings suggest that supportive strategies such as process writing, peer feedback, and reflection are effective in helping EFL students overcome writing anxiety and improve their academic writing.